Joint seasonality in geographic and ecological spaces, illustrated with a partially migratory bird. Issue 5 (19th May 2020) - Basille, Mathieu; Watling, James; Romañach, Stephanie; Borkhataria, Rena
Abstract: As most species live in seasonal environments, considering varying conditions is essential to understand species dynamics in both geographic and ecological spaces. Both resident and migratory species need to contend with seasonality and balance settling in favorable areas with tracking favorable environmental conditions during the year. We present an exploratory framework to jointly investigate a species' niche in geographic and ecological spaces, applied to wood storks ( Mycteria americana ), which are partially migratory wading birds, in the southeastern United States. We concurrently described monthly geographic distributions and climatic niches based on temperature and precipitation. Geographic distributions of wood storks were more similar throughout the year than were climatic niches, suggesting that birds stay within specific areas seasonally, rather than tracking areas of similar climate. However, wood storks expressed consistent selection of warm areas during the winter, and wet areas during the summer, indicating that the selection of seasonal ranges may be directly related to environmental conditions across the entire range. Our flexible framework, which simultaneously considered geographic and ecological spaces, suggested that tracking climate alone did not explain seasonal distributions of wood storks in breeding and non‐breeding areas.